25 lat komputeryzacji bibliotek kościelnych w Polsce – dorobek federacji FIDES - Witczak, Jerzy (Archiwa, Biblioteki i Muzea Kościelne, 2016)
This article outlines the origins of the Federation of Church Libraries FIDES with particular emphasis on the purpose for which it was created, i.e. the computerization of libraries and bibliographic information. Then the work presents the implementation of the main objective of the federation within 25 years of its existence. Finally, it focuses on the current state of work on the computerization of church library catalogues in Poland.